The Role of Cryptocurrency in Transnational Organized Crime: Legal Challenges and Opportunities for Global Law Enforcement Cooperation - Flora, Henny Saida; Maulidiana, Lina; Maulana, Sandrik Puji; Komara, Dadang; Putra, Hendri Darma (Jurnal Smart Hukum (JSH), 2025)
The rapid adoption of cryptocurrencies has significantly altered the landscape of transnational organized crime, offering new tools for money laundering, illicit trade, and cross-border value transfer. This qualitative research explores the multifaceted role of cryptocurrencies in facilitating criminal activities across borders, focusing on the legal challenges and opportunities for global law enforcement cooperation. Through systematic analysis of recent case studies, legal frameworks, and policy documents, the study identifies how criminal organizations exploit the anonymity, speed, and decentralized nature of cryptocurrencies to evade detection and prosecution. Key findings highlight persistent barriers such as jurisdictional fragmentation, technological gaps in law enforcement capabilities, and inconsistent regulatory standards across countries. However, the research also uncovers emerging opportunities, including the development of advanced blockchain analytics, harmonization of regulatory approaches (such as the EU’s MiCA regulation), and the formation of international task forces. The study concludes that effective countermeasures require enhanced multilateral cooperation, standardized legal protocols, and continuous capacity building within law enforcement agencies. By addressing these challenges, policymakers and practitioners can better disrupt the financial infrastructure of transnational organized crime in the digital age.